Proximate, minerals and anti-nutritional composition of daniellia oliveri (maje) tender leaves - Muhammad, Aliyu; Umar Birnin-Yauri, Abubakar; Moki Elinge, Cosmos; Rapheal Ige, Ayodeji (International Journal of Advanced Chemistry, 2022)
The Nutritional and anti-nutritional composition of tender leaves of Daniellia oliveri were analyzed in this study. The results of the proximate analysis were as follows, moisture content (78.67Â±2.31%), ash (4.67Â±0.29%), crude lipid (2.67Â±0.29%), crude protein (7.23Â±0.13%), crude fibre (2.33Â±0.29%), available carbohydrate (4.43Â±2.59%) and the energy value (70.67Â±12.45 kJ/kg). In elemental analysis, potassium has the highest concentration (3766.67Â±57.74 mg/100g), zinc (0.1502Â±0.00020 mg/100 g) is the lowest and lead (0.2352Â±0.00015 mg/100g). The anti-nutritional parameters analyzed includes; phytate (6.7592 mg/100g), oxalate (0.0023mg/100g), saponin (1.20mg/100g), tannin (430.80mg/100 g), hydrocyanic acid (122.73 mg/100g). The anti-nutrients to nutrients ratio show the bioavailability of some essential minerals, with the exception of [cyanides] and [tannin] in the tender leaves. These reach significant levels and are expected to reduce bioavailability of iron, magnesium and zinc in tender leaves.Â Â